Geographical variance in reporting of elective surgery for chronic pancreatitis. Issue 3 (March 2019) - Baltatzis, Minas; Jegatheeswaran, Santhalingam; Siriwardena, Ajith K.
Abstract : The selection of optimum surgical procedure from the range of reported operations for chronic pancreatitis (CP) can be difficult. The aim of this study is to explore geographical variation in reporting of elective surgery for CP. A systematic search of the literature was performed using the Scopus database for reports of five selected procedures for CP: duodenum-preserving pancreatic head resection, total pancreatectomy with islet autotransplantation (TPIAT), Frey pancreaticojejunostomy, thoracoscopic splanchnotomy and the Izbicki V-shaped resection. The keyword and MESH heading 'chronic pancreatitis' was used. Overall, 144 papers met inclusion criteria and were utilized for data extraction. There were 33 reports of duodenum-preserving pancreatic head resection. Twenty-one (64%) were from Germany. There were 60 reports of TPIAT, 53 (88%) from the USA. There are only two reports of TPIAT from outwith the USA and UK. The 34 reports of the Frey pancreaticojejunostomy originate from 12 countries. There were 20 reports of thoracoscopic splanchnotomy originating from nine countries. All three reports of the Izbicki 'V' procedure are from Germany. There is geographical variation in reporting of surgery for CP. There is a need for greater standardization in the selection and reporting of surgery for patients with painful CP.